2018
DOI: 10.2340/00015555-2842
|View full text |Cite
|
Sign up to set email alerts
|

Localized Scleroderma, Systemic Sclerosis and Cardiovascular Risk: A Danish Nationwide Cohort Study

Abstract: Recent findings indicate that patients with systemic sclerosis have an increased risk of cardiovascular disease. To determine whether patients with systemic sclerosis or localized scleroderma are at increased risk of cardiovascular disease, a cohort study of the entire Danish population aged ≥ 18 and ≤ 100 years was conducted, followed from 1997 to 2011 by individual-level linkage of nationwide registries. Multivariable adjusted Cox regression models were used to estimate the hazard ratios (HRs) for a composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Three studies were prospective and 4 were retrospective. Studies originated from Canada, [ 18 ] USA, [ 19 , 20 ] the UK, [ 20 ] Denmark, [ 21 , 22 ] and Taiwan. [ 23 , 24 ] The 7 studies included a total of 14,813 SSc patients and 5,506,836 controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were prospective and 4 were retrospective. Studies originated from Canada, [ 18 ] USA, [ 19 , 20 ] the UK, [ 20 ] Denmark, [ 21 , 22 ] and Taiwan. [ 23 , 24 ] The 7 studies included a total of 14,813 SSc patients and 5,506,836 controls.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] As to the comparability of cohorts, the study by Hesselvig et al was rated with a high risk of bias because the age and sex were not matched between SSc patients and control cohorts. [ 21 ] All 7 included cohort studies were determined to have a low risk of bias in the domain of adequacy of follow-up of cohorts because the durations of follow-up exceeded 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to other systemic diseases of connective tissue, such as rheumatoid arthritis and systemic lupus erythematosus, systemic sclerosis is linked to an elevated cardiovascular risk [14]. An analysis of data from the Danish Register showed that 25% of deaths of patients with systemic sclerosis were due to cardiovascular causes including myocardial infarction, heart failure and stroke, and further 26% of deaths were associated with other vascular complications such as scleroderma renal crisis and pulmonary hypertension [15,16].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Na podstawie analizy danych z duńskiego rejestru wykazano, że 25% zgonów pacjentów z twardziną układową wynika z przyczyn sercowo-naczyniowych, w tym zawału serca, niewydolności serca i udaru mózgu, a kolejne 26% zgonów wiąże się z innymi powikłaniami naczyniowymi, np. twardzinowym przełomem nerkowym i nadciśnieniem płucnym [15,16].…”
Section: Twardzina Układowaunclassified
“…Системная склеродермия (ССД) -аутоиммунное заболевание соединительной ткани с характерным поражением кожи, сосудов, опорно-двигательного аппарата и внутренних органов (легких, сердца, пищеварительного тракта, почек), в основе которого лежат нарушения микроциркуляции, воспаление и генерализованный фиброз [1]. Согласно многочисленным исследованиям при ССД повышен риск сердечно-сосудистых заболеваний и кардиоваскулярных катастроф [2][3][4]. В том числе и артериальная гипертензия (АГ) обнаруживается значительно чаще, чем в общей популяции [5,6].…”
unclassified